Temperature dependence for improving the accuracy of an electromagnetic microforce generating machine. (December 2021) - Zhu, Junfang; Hayashi, Toshiyuki; Ogushi, Koji
Abstract: This paper reported the relation of residual magnetic flux density and temperature of the neodymium magnets in electromagnetic microforce generating machine developed by referring to the principle of the Kibble balance at NMIJ, AIST. The residual magnetic flux density is affected by temperature fluctuations. The temperature coefficient of residual magnetic flux density was determined as −0.084%/°C. For improving the accuracy of the electromagnetic microforce generating machine, a temperature control system is being developed. Measurement of the device eigenvalue (number of the rectangular coil turns × residual magnetic flux density × area of rectangular coil) and temperature will be conducted.